PENDEKATAN STREAM (SCIENCE-TECHNOLOGY-RELIGION-ENGINEERING-ARTS-MATHEMATICS) MEMBEKALKAN KEBIASAAN BERPIKIR MAHASISWA - Tri Wahyu Agustina; Nuryani Y Rustaman; Riandi Riandi; Widi Purwianingsih (EDUSAINS, 2020)
THE STREAM APPROACH (SCIENCE-TECHNOLOGY-RELIGION-ENGINEERING-ARTS-MATHEMATICS) PROVIDES STUDENTS 'THINKING HABITSAbstractThis research develops an Applied Biology learning program using a science-technology-religion-engineering-arts-mathematics (STREAM) approach that can equip students with habits of mind. These thinking habits include systems thinking skills. The Applied Biology learning content includes compost making, nata de soya making, and biopesticides making. The research was carried out in the Microbiology course on the topic of Applied Microbiology. During the lectures, the learning process combines the 3Es learning cycle model (exploration-explanation-expansion phase), Jigsaw-type cooperative, and a combination of various learning methods. Students are trained in scientific process skills and designing /engineering skills. The products of the program consisted of modifications to the syllabus and the microbiology course matrix, performance tasks on students' worksheet, the STREAM approach scheme, system thinking skills' question instruments, concept map rubrics and scores. The resul indicate that system thinking skills in Applied Biology learning content could be equipped to students using the STREAM approach. AbstrakPenelitian mengembangkan program pembelajaran Biologi Terapan menggunakan pendekatan science-technology-religion-engineering-arts-mathematics (STREAM) yang dapat membekalkan kebiasaan berpikir. Kebiasaan berpikir tersebut diantaranya keterampilan berpikir sistem (KBS). Konten Biologi Terapan antara lain pembuatan kompos, nata de soya, dan biopestisida. Penelitian dilaksanakan pada perkuliahan Mikrobiologi pada pokok bahasan Mikrobiologi Terapan. Selama pembelajaran memadukan model siklus belajar 3Es (fase eksplorasi-pengenalan konsep-aplikasi konsep), kooperatif tipe Jigsaw, dan kombinasi metode belajar. Mahasiswa dilatihkan keterampilan proses saintifik dan mendesain (engineering). Produk program terdiri dari modifikasi pada silabus dan modifikasi matriks perkuliahan Mikrobiologi, tugas kinerja (task) pada lembar kerja mahasiswa (LKM), skema pendekatan STREAM, instrument soal KBS, dan skor beserta rubrik peta konsep. Hasil penelitian mengidikasikan bahwa KBS dapat dibekalkan kepada mahasiswa menggunakan pendekatan STREAM.